2020
DOI: 10.2112/jcoastres-d-19-00058.1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling for Hydrodynamics and Near-Surface Flow Patterns of a Tidal Confluence

Abstract: Because of the flow influx of tributaries, a confluence forms a unique environment carrying interesting hydrodynamic features and other attributes. The understanding of flow behavior here is important, particularly if it is on a tidally influenced channel in a harbor metropolitan. Because of communal requirements, there is a possibility of building wading structures, which may interplay with the flow in this zone. The knowledge of unidirectional river or flume confluences so far is not readily applicable for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Both of these conceptual models are physically combined, as shown in Figure 4. Field investigations [5,21,22], laboratory experiments [6,[23][24][25], and numerical simulations [14,[26][27][28][29][30], complementing each other, are common methods to help understand the morpho-dynamics of a confluence. Bradbrook [31] suggested that combining all three methods would help to understand the confluences more comprehensively.…”
Section: Items Non-tidal Confluence Tide-driven Confluencementioning
confidence: 99%
See 4 more Smart Citations
“…Both of these conceptual models are physically combined, as shown in Figure 4. Field investigations [5,21,22], laboratory experiments [6,[23][24][25], and numerical simulations [14,[26][27][28][29][30], complementing each other, are common methods to help understand the morpho-dynamics of a confluence. Bradbrook [31] suggested that combining all three methods would help to understand the confluences more comprehensively.…”
Section: Items Non-tidal Confluence Tide-driven Confluencementioning
confidence: 99%
“…As a result, the flow patterns in terms of the conventional flow zone definitions are different. Unlike unidirectional confluences, there are limited references available regarding the tidal confluence flow patterns, and its complexity has not drawn much attention [14,18,28].…”
Section: Tidal Flow Pattensmentioning
confidence: 99%
See 3 more Smart Citations